Pyramid Population Prediction using Age Structure Model - Heni Widayani; Nuning Nuraini; Anita Triska (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Population composition in a country by sex and age-structure often illustrated through the Population Pyramid. In this study, an age-structure model will be constructed to predict the population pyramid shape in the coming year. It is assumed that changes in population are affected by natality and mortality number in each age group, ignoring migration rates. The proposed age structure model formulated as a first-order partial differential equation with the non-negative initial condition. The boundary condition is given by the number of births which is proportional to the number of women at childbearing age. Then, this age structure model implemented utilizing United Nations Data to predict population pyramids of Indonesia, Brazil, Japan, the USA, and Russia. The population pyramid prediction of the five countries shows different characteristics, according to whether it is a developing or developed country. The results of this study indicate that the age structure model can be used to predict the composition of the population in a country in the next few years. Indonesia is predicted to be the highest populated country in 2066, compared to the other four countries. This result can be used as a reference for the government to plan policies and strategies according to age groups to control population explosion in the future.